Parenting Children with Cystic Fibrosis: Developmental Acquisition of Expertise. Issue 7 (18th September 2022) - Tluczek, Audrey; Grob, Rachel; Warne, Emily; Van Gorp, Stacy; Greene, Lisa; Homa, Karen
ABSTRACT: Objective: This study was designed to increase our understanding of parents' experiences managing the needs of their children with cystic fibrosis (CF) and to identify potential gaps in services. Method: We used grounded dimensional analysis of anonymous survey data obtained from a quality improvement initiative conducted by the Cystic Fibrosis Foundation (CFF). The Patient and Family Experience of Care (PFEC) survey was administered continuously at 125 CF care centers throughout the United States in 2017. The subsample of data for this study was completed by 80 parents/caregivers of children with CF (younger than 18 years). Results: Two unifying themes emerged from parents' survey responses: (1) parents' expertise expands continually as they learn and adapt to changes in their children's maturity or health and (2) parental expertise is sometimes visible or invisible to clinicians. Parents' expertise evolved with their children's development. Visible to care teams was at-home care, e.g., respiratory treatments and medications. Less visible were intangible management activities, e.g., social processes, emotions, and concerns that were omnipresent for parents but seldom disclosed to or seen/recognized by clinicians. Themes, such as the quality of encounters with care teams, progressive nature of CF, and hope derived from advances in research, were associated with specific contextual factors. Conclusion: The findings expand our understanding of lived parental experiences of CF across childhood and offer direction for future quality improvement and research. Online parent surveys offer a valuable tool to identify unmet needs across subgroups of families affected by chronic childhood health conditions.